(untitled) (gjstudies, 2020)
This research presents a novel conceptual framework that repositions internal auditing from a compliance-focused function to a strategic governance catalyst throughthe integration of predictive analytics, behavioral economics, and network theory. Traditional approaches to internal auditing have largely emphasized retrospective verification and regulatory adherence, creating a reactive posture that limits value creation.Our study introduces the Governance Synergy Model (GSM), which reconceptualizesinternal audit as a dynamic, anticipatory system that strengthens corporate governance through three innovative mechanisms: predictive risk intelligence, behavioralgovernance interventions, and network resilience enhancement. We develop a methodology combining agent-based modeling of governance networks with machine learning analysis of audit trail data to simulate governance outcomes under varying auditapproaches. Results from computational experiments demonstrate that the GSM approach increases governance effectiveness by 42% compared to traditional audit modelswhile reducing governance failures by 67% in simulated stress scenarios. The frameworkuniquely addresses the emergent complexity of modern corporate structures, where traditional linear governance models prove inadequate. Our findings reveal that internalaudit functions adopting predictive-analytic capabilities can identify governance vulnerabilities 3.2 times earlier than conventional methods, enabling proactive intervention. Furthermore, we demonstrate how behavioral insights applied to audit processescan improve board decision-making quality by 28% through cognitive bias mitigation.This research contributes original theoretical foundations for next-generation internalauditing and provides practical implementation pathways for organizations seeking totransform their governance architectures. The study establishes that internal auditing,when reconceptualized through our integrative framework, becomes a central mechanism for governance resilience rather than merely a verification function, offering novelinsights for both academic research and professional practice in corporate governance.